Analisis Sistem Bagi Hasil Pendapatan dalam Pandangan Ekonomi Syariah - Rayhan Nur Fauzi; Arif Rembang Supu; Mukhtar Mukhtar (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the business partnership practice through a mudharabah contract between a capital owner and a business manager at ACC Rahmat Store, with a focus on unilateral contract changes from the perspective of Islamic economics. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The results indicate that the unilateral shift in operational financing responsibilities by the capital owner, without mutual consultation or contract renewal, violates the principles of fairness, trust, and consent embedded in mudharabah contracts. This practice contradicts DSN-MUI fatwas and fundamental Islamic jurisprudence. The findings highlight the need for a thorough understanding of sharia-based contract structure and the necessity of tajdid al-‘aqd (contract renewal) in any substantial contractual changes.